Multilingualism 2.0: language policies and the use of online translation tools on global platforms - Cenni, Irene (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
At present, the existing 2.0 Web is far more multilingual than was ever anticipated in the early days of the Internet (Hale, 2014; Hale & Eleta, 2017). Indeed, the increasing variety of languages is a phenomenon that signals the end of the first stages of the digital era in which the Internet was characterized by English-language dominance (Leppänen & Peuronen, 2012). This study primarily aims to present the emerging topics in multilingual research that focus on 2.0 platforms. It presents a literature review and discusses a number of multilingual strategies adopted by different platforms. Five popular platforms have been considered, namely Wikipedia, Facebook, Instagram, Booking.com and TripAdvisor, with close attention paid to travel platforms (and TripAdvisor, in particular). For 2.0 platform providers such as TripAdvisor, multilingualism constitutes a challenge. Typically, these platforms do not opt for an English-only rule, but rather develop linguistic policies in order to accommodate their multilingual users (Cenni & Goethals, 2017). The case of TripAdvisor is particularly striking, not least because it is characterized by the coexistence of two divergent multilingual strategies on the same platform.